Phase II trial of CDK4/6 inhibitor palbociclib in advanced sarcoma based on mRNA expression of CDK4/CDKN2A - Javier Martin-Broto; Jeronimo Martinez-Garcia; David S. Moura; Andres Redondo; Antonio Gutierrez; Antonio Lopez-Pousa; Javier Martinez-Trufero; Isabel Sevilla; Roberto Diaz-Beveridge; Maria Pilar Solis-Hernandez; Amancio Carnero; Marco Perez; et al. (Signal Transduction and Targeted Therapy, 2023)
Abstract Cyclin-dependent kinases 4 and 6 (CDK4/6) inhibitors demonstrated activity in terms of progression-free survival (PFS) in advanced dedifferentiated liposarcoma (DD-LPS), a sarcoma with CDK4 amplification. CDK4 overexpression is by far more common than amplification in sarcomas and it might be a rational target for CDK inhibitors. Preclinical investigators of this study found that CDK4 overexpression, while not of CDKN2A, was the most consistent predictive factor for palbociclib efficacy in sarcomas. Advanced adult-type soft-tissue sarcoma, excluding DD-LPS, or bone sarcoma patients, progressing after at least one systemic line, whose tumors overexpressed CDK4, but not CDKN2A at baseline biopsy, were accrued in this single-arm phase II trial (EudraCT number: 2016-004039-19). With the main endpoint of a 6-month PFS rate, 40% was considered promising in this population. Palbociclib was administered orally at 125 mg/day for 21 days in 28-day cycles. A total of 214 patients with 236 CDK4/CDKN2A determinations were assessed for prescreening, archival material (141), and screening, baseline biopsy (95). There were 28 (29%) with favorable mRNA profiles from 95 screened patients at baseline. From 23 enrolled patients, 21 evaluable, the 6-month PFS rate was 29% (95% CI 9–48), and there were 6 patients out of 21 with a PFS longer than 6 months. The median PFS and overall survival were 4.2 (95% CI 3.6–4.8) and 12 (95% CI 8.7–15.4) months, respectively. Translational research showed a significant correlation between CDK4 mRNA and protein expression. Palbociclib was active in a variety of sarcoma subtypes, selected by CDK4/CDKN2A, and deserves further investigation in the sarcoma context.